Investigation of CNT modification of epoxy resin in CFRP strengthening systems. Issue 4 (29th September 2014) - Dehghan, Masoud; Al‐Mahaidi, Riadh; Sbarski, Igor
Abstract : The use of carbon fiber‐reinforced polymers (CFRPs) to reinforce old structures has become popular in recent years. In this study, the chemical structure of the epoxy resin used as the bonding agent in the CFRP strengthening system was modified by dispersing multi‐walled carbon nanotubes (MWCNTs) in order to improve the performance of the strengthening system. Composites were fabricated with different mixing orders employing the solvent‐assisted dispersion method and ultrasonic mixing. Thermogravimetric analysis, dynamic mechanical analysis, and tensile tests were conducted to investigate the effect of CNT dispersion and fabrication method on the thermal and mechanical properties of epoxy composite. In addition, the temperature‐dependent tensile behavior of fabricated composites was studied by performing tensile tests at elevated temperatures. The morphology of CNT/epoxy composites was characterized using scanning electron microscopy (SEM). Fourier transform infrared (FTIR) was also used to show the influence of solvent on the molecular structure of composites. Based on the experimental results, the decomposition temperature of the epoxy resin was heightened by 15°C as a result of solvent‐assisted dispersion of nanotubes. However, the glass transition temperature ( T g ) was slightly reduced due to the solvent effect. FTIR analysis revealed that the solvent negatively affects the curing process of epoxy composite. A considerable enhancement was recorded in the tensile properties as a result of CNT infusion. This was attributed to the homogeneous dispersion of nanotubes which was shown by SEM images. Using solvent to disperse nanotubes led to the reduction of tensile strength of the epoxy composite at elevated temperature due to the lower T g . POLYM. COMPOS. 37:1021–1033, 2016. © 2014 Society of Plastics Engineers